The Perils of Inconsistent Use of ICT-Related Terminology in School Textbooks - Nikolche Mickoski (European Scientific Journal, ESJ, 2021)
This paper analyses the consistency in use of appropriate ICT-related terminology in school textbooks in elementary and secondary schools that are approved by the National Textbook Committee and published by the Ministry of Education and Science of the Republic of North Macedonia. Analysis shows that ICT-related terminology is used inconsistently, and sometimes incorrectly, in the analysed textbooks. Consistent use of correct and appropriate terminology in all the textbooks will enable pupils to acquire the correct terminology and use it correctly.